การพัฒนาระบบการวางแผนความต้องการกำลังการผลิต - สุรชาติ เอาเจริญพร (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
Production system consists of four main factors: inventory control system, production planning system, material requirements planning system, and capacity requirements planning system. It was found that the third factor is always considered as the most important factor. Because manufacturers do not want to face with the problems of raw material shortage. Most manufacturers ignore their existing production capacity, this leads to the waste of both labor force and time. However, if the capacity requirements planning is planned in accordance with the material requirements planning, the efficiency of the production system should increase because the capacity requirements planning will evaluate the required production capacity within the production system. Data from capacity plan will assist in the adjustment of existing production capacity. The design of capacity requirements planning system in this thesis comprises two parts: the rough-cut capacity planning which calculates the production capacity required from the master production plan; and the capacity requirements planning which calculates the production capacity required from material requirements plan. The system design starts from analyzing the current production system in order to get both the data flow diagram arid the document flow diagram, together with the problems of current production system. After that, the production stage of the new system was designed, followed by the development of the program for capacity requirements planning system. It is emphasized that this program should be easy to use, provide correct data, and quick calculation for production capacity plan. Data from SIGMA PAINTS (THAILAND) Co., Ltd. is used a case study. The result shows that the developed capacity requirements planning system has data integrity, reduced data redundancy and time comparing to the existing production.